2018
DOI: 10.3390/cancers10070231
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Shuffling: deVV5, a Novel Chimeric Poxvirus with Improved Oncolytic Potency

Abstract: Oncolytic virus (OV) therapy has emerged as a promising approach for cancer treatment with the potential to be less toxic and more efficient than classic cancer therapies. Various types of OVs in clinical development, including Vaccinia virus (VACV)-derived OVs, have shown good safety profiles, but limited therapeutic efficacy as monotherapy in some cancer models. Many different methods have been employed to improve the oncolytic potency of OVs. In this study, we used a directed evolution process, pooling diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The Copenhagen strain of VACV was originally used as a smallpox vaccine in Denmark and the Netherlands. Probably due to variations in the expression or functionality of different virulence genes between strains, in vitro and in vivo preclinical studies have recently shown that the Copenhagen strain has a more potent oncolytic viral activity against human tumor cells than the Wyeth and the WR strains,46, 47 the original strains of oncolytic VACVs that are currently in clinic. These results suggest that Copenhagen-based VACV should be more effective at controlling tumor growth in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The Copenhagen strain of VACV was originally used as a smallpox vaccine in Denmark and the Netherlands. Probably due to variations in the expression or functionality of different virulence genes between strains, in vitro and in vivo preclinical studies have recently shown that the Copenhagen strain has a more potent oncolytic viral activity against human tumor cells than the Wyeth and the WR strains,46, 47 the original strains of oncolytic VACVs that are currently in clinic. These results suggest that Copenhagen-based VACV should be more effective at controlling tumor growth in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…All poxviruses used were wild type and have been described in detail in Ricordel et al (17, 35, 36), except for the vaccinia viruses of Copenhagen strain that were either wild type, doubly deleted of thymidine kinase and ribonucleotide reductase (TK − RR − ), or triply deleted of TK, RR, and M2L (TK − RR − M2L − ). Modified vaccinia virus Ankara (MVA) was also used in some experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Another interesting strategy is to generate novel chimeric poxviruses via homologous recombination of different strains of VV or poxviruses or by natural selection in cancer cells themselves. Erbs and associates mixed four strains of VVs and generated deVV5, a novel chimeric poxvirus with improved oncolytic potency in human cancer cells [113]. Chen and colleagues generated another virus, CF189, by mixing different species of poxviruses; yielding a chimeric OV that is therapeutically effective in triple negative breast cancer models, even at low viral doses [114].…”
Section: Biology Of Vaccinia Virusmentioning
confidence: 99%